The influence of home and school environments on alcoholic beverages, tobacco and marijuana consumption by adolescents in Prague and Brno - Honsnejmanová, Irena; Jarolímek, Jan (Geographica Pannonica, 2021)
Excessive use of alcoholic beverages, tobacco or marijuana is problematic not only for adults, but in some countries, it is a significant problem for children. However, the reasons for differences in children’s risk behavior, as well as the reasons for risk behavior itself, are not yet fully understood. In this article we focused on the association between the quality of the school and home environment (and their surroundings) as perceived by children themselves and their risk behavior in relation to the use of selected substances. We worked with group of 343 9th grade primary school pupils in different types of neighborhoods. The results of our research show that at least some aspects of the quality of the physical environment have an impact on children’s risk behavior.